Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa - Rodríguez-Estévez, V; García Martínez, A; Mata Moreno, C; Perea Muñoz, J M; Gómez Castro, A G (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value
Keywords: fatty acids; iberian pig; Montanera; Quercus ilex; Quercus suber; Sus scrofa

Dimensiones y características nutritivas de las bellotas de los Quercus de la dehesa - Rodríguez-Estévez, V.; García Martínez, A.; Mata Moreno, C.; Perea Muñoz, J. M.; Gómez Castro, A. G. (Arch. Zootec, 2008)
Acorns production of Quercus (Q. ilex, Q. suber, etc.) is an important feeding resource in the dehesa during autumn-winter. Acorn weight, size and shape present a lot of variability between species, species, individuals and areas. Also composition is variable and is influenced by its own maturation process and external agents (humidity, parasites, etc.). Op.osite, shell and cotyledons proportions show higher homogeneity. Shell composition has a very high level of tannins and lignin, which affects its digestibility. Kernel has a very high level of glucids (80% of DM) and lipids (5-10% of DM) with a oleic acid content up.er 60%, however protein level is very low (4-6% of DM). Many wild and domestic species eat acorns; however, in the dehesa, acorns are used to feed fattening Iberian pigs because this breed is the single one capable of peeling them and rises a high commercial value
Keywords: fatty acids; iberian pig; Montanera; Quercus ilex; Quercus suber; Sus scrofa

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernandez-Llario, P.; Mateos-Quesada, P.; Silvério, A.; Santos, P. (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Habitat effects and shooting techniques on two wild boar (Sus scrofa) populations in Spain and Portugal - Fernández-Llario, P; Mateos-Quesada, P; Silvério, A; Santos, P (Zeitschrift für Jagdwissenschaft, 2003)
In the last decades, wild boar (Sus scrofa) distribution has increased world-wide, the Iberian Peninsula being no exception. The wild boar now inhabits almost the entire Iberian territory, where today it is one of the most important big game species. In this paper, for the first time, bag analysis from two ecological different regions are presented and compared to the employed hunting techniques. One represents the well-preserved Mediterranean forests of south-western Spain, the other, located in the south of Portugal, is a farmland with interspersed forest areas. Our results indicate a stronger hunting intensity and also a higher wild boar population density in the Portuguese study areas. The stronger hunting intensity may result in a younger wild boar population. We also found considerable differences between the shooting techniques used in both regions and those employed in the north-east of the peninsula. It does therefore not seem advisable to directly compare bag statistics from different regions of the Iberian peninsula.
Keywords: habitats; Mediterranean; Populations; Portugal; shooting techniques; Spain; Sus scrofa; Wild boar

Cynegetical development of the French Mediterranean ``matorral'' scrublands: Case of wild ungulates - Maillard, D; Melac, O; Gaudin, J C; Vassant, J (GIBIER FANE SAUVAGE - GAME AND WILDLIFE, VOL 15 (SPECIAL NUMBER PTS 2 AND 3) 1998, 1998)
Since the beginning of the seventies, the marorrals (garrigues, maquis, and holly oak, Quercus ilex, copses) are slowly being colonized by roe deer, Capreolus capreolus, white wild boar; Sus scrofa, populations are stongly increasing. This phenomenon is mainly due to a relative low hunting pressure compared to the potential huntable population, to the disappearance of traditional farming practices (rural abandonment) causing the matorrals to extend, to the compensations paid to farmers since 1969, and to an increase in food resources (ageing of holly oak copses). As for red deer, Cervus elaphus, its population is increasing very slowly: The uncontrolled increase in wild boar populations is causing intolerable damages to farmers, especially in high-quality crops (arboriculture, vines, market-garden crops), which have been expanding since the productive lands in the bottom of the valley are being cultivated and agricultural techniques have improved. In the years to come, the ungulates frequenting the garrigue may become a harvestable resource if the two main sympatric species (wild boar and roe deer) which are occupying areas of some 30,000 ha, are wisely managed and the following parameters are taken into account : - amount of food produced in the habitats (annual mast crops); - damage control by controlled hunting in each massif, and damage prevention (protection or dissuation); - appropriate management of ungulate territories and the effective control of their populations based on hunting bag analyses in the middle and at the end of the hunting season. Most of ail it is important that before applying the ``population/environment/damage{''} model in each massif or management unit, clear management objectives be defined in agreement with the farmers.
IUGB XXIIIrd Congress, LYON, FRANCE, SEP 01-06, 1997
Keywords: roe deer; Sus scrofa; Wild boar; wild ungulate